IMPLEMENTATION OF ISO 9126 IN THE QUALITY TEST OF THE M-PASSPORT APPLICATION AT THE CLASS I NON-TPI TANGERANG IMMIGRATION OFFICE - I.A Prabadhi; Mila Rosmaya; alya Silvia (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2022)
In order to improve services to the community, the Directorate General of Immigration has utilized information technology in the form of a service information system for the community. The purpose of this study is to measure the quality of the information system for immigration services at the Tangerang Immigration Office according to ISO 9126. Collection method the data used is simple observation, interviews, and quantitative in the form of filling out questionnaires. The validity and reliability test uses SPSS 26. The results of this study indicate that the measurement of the quality of patient service information systems carried out with the ISO 9126 standard is obtained as follows: Functionality variable is 95%, Reliability variable is 90.7%, Usability variable is 90%, Variable the efficiency is 93%, the maintainability variable is 91% and the portability variable is 95.7%. And through the percentage of due diligence, it can be concluded that the use of the M-Passport application in immigration services for passport applicants at the Immigration Office Class I Non TPI Tangerang has fulfilled the ISO 9126 standard with the percentage obtained an average actual score of 91.99% or an average criterion "Very good".